Plasma CXCL9 and CXCL10 at allograft injury predict chronic lung allograft dysfunction. Issue 9 (15th June 2022) - Shino, Michael Y.; Todd, Jamie L.; Neely, Megan L.; Kirchner, Jerry; Frankel, Courtney W.; Snyder, Laurie D.; Pavlisko, Elizabeth N.; Fishbein, Gregory A.; Schaenman, Joanna M.; Mason, Kristen; Kesler, Karen; Martinu, Tereza; et al.
Abstract: Histopathologic lung allograft injuries are putative harbingers for chronic lung allograft dysfunction (CLAD). However, the mechanisms responsible are not well understood. CXCL9 and CXCL10 are potent chemoattractants of mononuclear cells and potential propagators of allograft injury. We hypothesized that these chemokines would be quantifiable in plasma, and would associate with subsequent CLAD development. In this prospective multicenter study, we evaluated 721 plasma samples for CXCL9/CXCL10 levels from 184 participants at the time of transbronchial biopsies during their first‐year post‐transplantation. We determined the association between plasma chemokines, histopathologic injury, and CLAD risk using Cox proportional hazards models. We also evaluated CXCL9/CXCL10 levels in bronchoalveolar lavage (BAL) fluid and compared plasma to BAL with respect to CLAD risk. Plasma CXCL9/CXCL10 levels were elevated during the injury patterns associated with CLAD, acute rejection, and acute lung injury, with a dose–response relationship between chemokine levels and CLAD risk. Importantly, there were strong interactions between injury and plasma CXCL9/CXCL10, where histopathologic injury associated with CLAD only in the presence of elevated plasma chemokines. We observed similar associations and interactions with BAL CXCL9/CXCL10 levels. Elevated plasma CXCL9/CXCL10 during allograft injury may contribute to CLAD pathogenesis and has potential as a minimally invasive immune monitoring biomarker. Abstract : This prospective multicenter study finds an association between levels of CXCL9 and CXCL10 in both plasma and bronchoalveolar lavage fluid during allograft injury in the first year after lung transplantation. Diamond and Shtraichman comment on page 2133